2021
DOI: 10.3390/antiox10081275
|View full text |Cite
|
Sign up to set email alerts
|

Isoorientin Attenuated the Pyroptotic Hepatocyte Damage Induced by Benzo[a]pyrene via ROS/NF-κB/NLRP3/Caspase-1 Signaling Pathway

Abstract: Isoorientin (Iso), a natural bioactive flavonoid, possesses significant anti-tumor and anti-oxidant activities. Benzo[a]pyrene (BaP) is a food processing injurant with carcinogenicity, teratogenicity, and genotoxicity. Our preliminary study demonstrates that Iso attenuated the pyroptotic hepatocyte damage induced by BaP; however, the molecular mechanism remains unknown. The present study showed that Iso reduced the increase caused by BaP in the overflow of LDH, NO, and the electrical conductivity and the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…Phosphorylation and nuclear translocation of P65 are implicated in NLRP3 inflammasome activation and inflammatory response regulation. [17][18][19][20] Our data showed that CRIZO treatment activated P65 in hepatic cells. These results demonstrated that CRIZO triggered hepatocyte pyroptosis via NF-κB/NLRP3/GSDMD pathway.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Phosphorylation and nuclear translocation of P65 are implicated in NLRP3 inflammasome activation and inflammatory response regulation. [17][18][19][20] Our data showed that CRIZO treatment activated P65 in hepatic cells. These results demonstrated that CRIZO triggered hepatocyte pyroptosis via NF-κB/NLRP3/GSDMD pathway.…”
Section: Discussionsupporting
confidence: 51%
“…As anticipated, CRIZO markedly promoted phosphorylation and nuclear translocation of P65 (Figure 2C,D ), which favoured the formation of NLRP3 inflammasome. 17 , 18 , 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of NLRP3 is also partially related to damaged mitochondria where the bulk of reactive oxygen species (ROS) is produced (Mangan et al, 2018; Swanson, Deng, & Ting, 2019; Wang et al, 2021). There is accumulating evidence that application of mitochondrial active oxygen scavenger, mito‐TEMPO, can inhibit NLRP3 inflammasome activation (Heid et al, 2013; H. Li et al, 2021), and it has been shown that severe acute pancreatitis is alleviated in NLRP3 −/− mice (Sendler et al, 2020). In addition, Li et al have demonstrated that inhibition of NLRP3 activity can reduce hepatocyte injury (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence that application of mitochondrial active oxygen scavenger, mito‐TEMPO, can inhibit NLRP3 inflammasome activation (Heid et al, 2013; H. Li et al, 2021), and it has been shown that severe acute pancreatitis is alleviated in NLRP3 −/− mice (Sendler et al, 2020). In addition, Li et al have demonstrated that inhibition of NLRP3 activity can reduce hepatocyte injury (Li et al, 2021). Thus, inhibition of NLRP3 inflammasome may be an important therapeutic target for LPS‐induced ALI, but its potential mechanism remains to be explored.…”
Section: Introductionmentioning
confidence: 99%